Hindfoot malalignment in adults with haemophilic ankle arthropathy: The importance of early detection and orthotic treatment. Issue 3 (21st January 2019) - De la Corte‐Rodriguez, Hortensia; Rodriguez‐Merchan, Emerito Carlos; Alvarez‐Roman, Maria Teresa; Martin‐Salces, Monica; Jimenez‐Yuste, Victor
Abstract : Introduction: Haemophilic arthropathy (osteoarthritis secondary to haemophilia) of the ankle may result in painful hindfoot malalignment. Purpose: To analyse hindfoot alignment in subjects with haemophilic arthropathy of the ankle and evaluate the response (improvement of pain, function and alignment) to the orthotic treatment prescribed in patients with malalignment. Methods: The study included 163 patients with haemophilia, all of them over 16 years of age. Hindfoot alignment and footprint were analysed in patients with and without haemophilic arthropathy of the ankle (as determined by the Pettersson score). Response to the use of an orthosis was evaluated at 6 months by means of the AOFAS Ankle‐Hindfoot Scale. Results: Fifty‐six (59.5%) patients with haemophilic arthropathy presented with concomitant hindfoot malalignment. The most common abnormality was a valgus alignment combined with a neutral footprint. In 14 cases, valgus was associated with a pes planu s or a pes cavus . Only 5 patients without haemophilic arthropathy (7.2%) presented with some form of malalignment. The differences between the groups were statistically significant. The probability of having malalignment increased with the degree of arthropathy. Patients with haemophilic arthropathy and malalignment were treated with an orthosis, with insoles as the most commonly used alternative (86%). Such treatment significantly improved patients' pain and function‐related scores on the AOFAS Ankle‐Hindfoot Scale. Conclusion: Given the high rates of valgus malalignment in subjects with haemophilic arthropathy of the ankle, and the good response rates obtained following individualised orthotic treatment, it seems reasonable to routinely evaluate hindfoot alignment in this group of patients.